BAFFR controls early memory B cell responses but is dispensable for germinal center function - Lau, Angelica W.Y. (J Exp Med, 2020)
The TNF superfamily ligand BAFF maintains the survival of naive B cells by signaling through its surface receptor, BAFFR. Activated B cells maintain expression of BAFFR after they differentiate into germinal center (GC) or memory B cells (MBCs). However, the functions of BAFFR in these antigen-experienced B cell populations remain unclear. Here, we show that B cell–intrinsic BAFFR does not play a significant role in the survival or function of GC B cells or in the generation of the somatically mutated MBCs derived from them. Instead, BAFF/BAFFR signaling was required to generate the unmutated, GC-independent MBCs that differentiate directly from activated B cell blasts early in the response. Furthermore, amplification of BAFFR signaling in responding B cells did not affect GCs or the generation of GC-derived MBCs but greatly expanded the GC-independent MBC response. Although BAFF/BAFFR signaling specifically controlled the formation of the GC-independent MBC response, both types of MBCs required input from this pathway for optimal long-term survival.